Focus attention and relationship with the performance of some basic skills on the balance-shifting device in your women’s technical gym. - Jabbar Mahmood, Sanarya (International Journal of Psychosocial Rehabilitation, 2020)
The first section included the introduction and the importance of research, as attention and focus are two of the important mental abilities that the learner needs in your gym during performance, which has an important role to play in evaluating performance, and gymnastics is one of the most comprehensive sports in focusing attention because it is self-reliant and self-assessment of the individual, whether player or learner, as well as the devices used that are difficult (difficult skills) for the learner. Focus and attention is one of the priorities of the sport of gymnastics devices, which negatively or positively affect the performance, and here lies the importance of research on the mental ability to focus attention on the player or educated for the sport of gymnastics on the devices and in the second part was the share of the methodology of research and its field procedures that the researcher used the descriptive method in the way of related relationships to suit the nature of the problem but the third part is the presentation and analysis and discussion of the results reached by the researcher and in the fourth part is what the researcher concluded from the results of the researcher User search and recommendations recommended in order to raise the search to the required level.